Immobilization of Streptavidin on a Plasmonic Au-TiO2 Thin Film towards an LSPR Biosensing Platform - Pereira-Silva, Patrícia (2022)
Optical biosensors based on localized surface plasmon resonance (LSPR) are the future of label-free detection methods. This work reports the development of plasmonic thin films, containing Au nanoparticles dispersed in a TiO2 matrix, as platforms for LSPR biosensors. Post-deposition treatments were employed, namely annealing at 400 °C, to develop an LSPR band, and Ar plasma, to improve the sensitivity of the Au-TiO2 thin film. Streptavidin and biotin conjugated with horseradish peroxidase (HRP) were chosen as the model receptor-analyte, to prove the efficiency of the immobilization method and to demonstrate the potential of the LSPR-based biosensor. The Au-TiO2 thin films were activated with O2 plasma, to promote the streptavidin immobilization as a biorecognition element, by increasing the surface hydrophilicity (contact angle drop to 7°). The interaction between biotin and the immobilized streptavidin was confirmed by the detection of HRP activity (average absorbance 1.9 ± 0.6), following a protocol based on enzyme-linked immunosorbent assay (ELISA). Furthermore, an LSPR wavelength shift was detectable (0.8 ± 0.1 nm), resulting from a plasmonic thin-film platform with a refractive index sensitivity estimated to be 33 nm/RIU. The detection of the analyte using these two different methods proves that the functionalization protocol was successful and the Au-TiO2 thin films have the potential to be used as an LSPR platform for label-free biosensors.